Vertical integration in industrial enterprises and distributed middleware. (2016) - Ismail, Ahmed; Kastner, Wolfgang
Recent advances in information, operations and networking technologies have brought forth many economical and organisational opportunities for industrial enterprises. One of the enabling pillars for the exploitation of these opportunities hinges predominantly on the design and introduction of frictionless vertical integration in enterprises. The paper presented concerns itself with the generation of autonomous middleware for vertical integration in existing or new industrial enterprises. Consequently, the paper discusses the main concerns of designing such middleware systems for typical enterprise infrastructure. Solutions from both the information and operations technology sectors are examined in light of said requirements with the aim of enhancing the current state of middleware solutions and industrial enterprises alike.